Bonding mechanism in direct laser deposition of 410L stainless steel - Zhao, Xuhe (Nanyang Technological University, 2022)
Based on the direct laser deposition technology (DLD), this study analyzes its working mechanism through some experiments, which are based on the deposition of A36 low carbon steel and 410L stainless steel powder. Through 31 groups of experiments with different parameters, the influence of basic parameters such as scanning speed, feed rate and laser power on the final deposition effect is analyzed. And the working area suitable for actual processing is obtained by drawing figures. The microstructure of the substrate, heat affected zone and cladding were analyzed by optical micrographs (OM), scanning electronic microscopy (SEM) and Energy Dispersive Spectrometer (EDS). Finally, the possibility whether 410L stainless steel powder can be deposited on aluminum alloy steel (6061) substrate by DLD was explored. Severe cracks, deformations and brittle intermetallics were observed, which indicated the difficulties of the bonding with aluminum and stainless steel using DLD. At last, three main bonding mechanism are concluded as brazing bonding, fusion bonding and intermetallic bonding.